Bezrobocie w skali kraju, województwa i powiatu poznańskiego - Kokociński, Maciej (Wydawnictwo Naukowe UAM, 2001)
The problem of unemployment affects all categories of families. In late years of the nineties the number o f the unemployed has increased on the job market. The unemployment has become one of the main factors responsible for destabilisation of structure and function of families. Despite ten years of analyses of unemployment problems there are still errors in the means of measuring the intensity and structure o f this problem. The characteristic feature of Polish kind of unemployment is its evolution. It considers quality as well as quantity changes. In the paper on unemployment we are going to analyse the problem on three layers i. e. the layer of state of province and district. The object of our analysis is contemporary situation of Poznan job market on the level of the province and district, based on local data collected by the district job office. Our results will prove that the intensity of negative agents connected with the lack of jobs and exclusion from social activities of a bigger and bigger social working groups.
Unemployment in the scale of the country, Poznan province and Poznan district